The Department of Continuing Professional Development (CPD) of BCPS - Ensuring the Proficiency & Competency of Health Professionals - Ara Nasreen, Shaikh Zinnat; Rabbani, Md Golam; Anwar, Sayeeda; Fatema, Kaniz (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 116-117